STUDY ABOUT CHARACTERISTICS PEOPLE LIVING WITH HIV (PLHIV) AND STIGMA BY HEALTH WORKERS OF PLHIV IN YOGYAKARTA - Indriani Indriani; Annisa Fitriana Damalita (Jurnal Kesehatan Karya Husada, 2015)
Background: Stigma and discrimination are recognized as the barrier in the prevention and treatment programs with HIV and AIDS (Cao et al., 2010). One in four people are still afraid to have direct contact with people who are HIV-positive and reported that they would actively avoid interacting with someone they know to be HIV-positive (Herek, Capitanio, & Widaman, 2002). Stigma does not just come from the family, the community, but also from health personnel.Objective and Methods: To identify the characteristics of people living with HIV (PLHIV) and health workers stigma against people living with HIV in the city of Yogyakarta. Research using analytic survey with cross sectional approach. A total of 82 samples were obtained from 487 PLHIV and 53 health personnel from the region Pukesmas City. Samples were taken by using the purposive random sampling.Results: There was a significant relationship between gender (p = 0.026), education (p = 0.015), religion (p = 0.005) against the perceived stigma of people with HIV. A total of 56.9% said getting the stigma of personnel health personnel.Suggestions Conclusion: There is still a stigma of health workers and in this case the policy support from the government in addressingsocio-cultural and psychological related to HIV and AIDS is very necessary. Communication and campaigns on HIV / AIDS in order to optimize the knowledge of health workers and the public in the hope of discriminatory behavior and stigma reduction. It is hoped that this campaign will promote the use of standard precautions and practice of health professionals.